Preliminary isolation report of aerobic magnetotactic bacteria in a modified nutrient medium - Chandrajit, Sharma, Gyan Prakash*; Balomajumder, (Recent Research in Science and Technology, 2011)
A modified nutrient medium was developed for isolation of magnetotactic bacteria. An aerobic strain of Magnetotactic bacteria (MTB) was successfully isolated in modified nutrient medium. Ferric quinate was used as the main iron source. Macroscopic and microscopic studies were performed to study the magnetotactic response of the isolated strain. Motility towards the externally applied magnetic field direction confirmed the isolated strain to be magnetotactic in nature. Scanning electron microscopic analysis was used to study the morphology, which shows rod like shape of isolated strain. Electron dispersive X ray diffraction analysis confirmed the presence of elemental carbon as a major constituent. Moreover, elemental iron and oxygen indicated the formation of magnetic material inside the bacterial cells. Vibrating Sample Magnetometer analysis is performed to reveal the magnetic characteristics of the isolated bacterial strain.